Korelasi Antara Dukungan Sosial Dan Self-Efficacy Terhadap Pemilihan Karir Siswa Kelas XI SMAN 3 Banjarmasin - Aminah; Rafiqoh; Eka Sri Handayani (Universitas Veteran Bangun Nusantara, 2025)
Career choice during senior high school is a crucial stage in adolescent development that often presents challenges, particularly in recognizing personal potential and receiving adequate support. This community service program aimed to assist eleventh-grade students of SMAN 3 Banjarmasin in strengthening self efficacy and social support to make more appropriate career decisions. The program employed a quantitative correlational design involving 223 students using validated and reliable scales of social support, self efficacy, and career choice. Data were collected through online questionnaires and analyzed statistically. The results showed that both social support and self efficacy were significantly related to students’ career choices, with self efficacy emerging as the dominant factor. The coefficient of determination of 28.9 percent indicated the substantial contribution of these variables to career choice variation. The solution offered highlights the need for schools and families to provide continuous support and organize structured career guidance programs to enhance students’ confidence in shaping their future careers.